Ask a question
0 0

what is the substition method for -3x+y=-2?

i need help with substition


Tutors, please sign in to answer this question.

2 Answers

The substitution method usually refers to a way to solve a system of equations.  Do you have a second equation?  If you do, the idea is to solve one equation for a variable, like y.  So solve equation 1 for y.  Then in equation 2, replace y with what it equals in equation 1.

It's a lot easier to explain with an actual example.  Maybe you can repost your question with the other equation...

If there were a second equation, you would isolate y in this equation and solve the 2nd equation for what x equals.  Here  -3x+y=-2, so move everything but the y over to the other side. So add 3x to both sides to isolate the y, -3x + 3x + y    = -2+3x, so y = -2+3x or y=3x-2, so everywhere where you see a y in the other equation you plug in 3x-2.  For example if the other equation was 2x + 3y = 16 the equation would become 2x + 3(3x-2) = 16.  I plugged in or substituted 3x-2 for y.  Then use the distributive property, so 2x + 9x - 6 = 16 then combine like terms 11x - 6 = 16,  (add 6 to both sides to isolate the variable) so 11x = 22, (divide by 11) so x = 2.  Plug the 2 in for x into y = 3x - 2 to solve for y, so y = 3(2) - 2, so y=4.